2005
DOI: 10.1007/s00432-005-0047-7
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 inhibitors cause G2/M arrest associated with the reduction of Cdc25C and Cdc2 in lung cancer cell lines

Abstract: Hsp90 inhibitor is thus a therapeutic tool for lung cancer based on its target proteins, which are involved in tumor progression and antiproliferative activity in lung cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 33 publications
(46 reference statements)
3
47
0
Order By: Relevance
“…However, the effects of the Hsp90 inhibition are very complex and depend on the biochemical features and molecular background of treated cells [42]. The reported cell cycle effects are mostly G1 and G2/M arrest [43][44][45][46]. Here, after GA treatment of MCF-7 cells, we observed the increased incidence of apoptosis and the decreased frequency of polyploid cells with the features of mitotic catastrophe.…”
Section: Discussionsupporting
confidence: 48%
“…However, the effects of the Hsp90 inhibition are very complex and depend on the biochemical features and molecular background of treated cells [42]. The reported cell cycle effects are mostly G1 and G2/M arrest [43][44][45][46]. Here, after GA treatment of MCF-7 cells, we observed the increased incidence of apoptosis and the decreased frequency of polyploid cells with the features of mitotic catastrophe.…”
Section: Discussionsupporting
confidence: 48%
“…A recent report has shown that GA and 17-AAG can cause a G 2 /M arrest that is associated with reduction of cdc25c and cdc2 in lung cancer cell lines (Senju et al, 2006). However, the authors did not study in detail the mechanism of downregulation of both cdc25c and cdc2 in these cell lines.…”
Section: Discussionmentioning
confidence: 95%
“…However, in many human tumor cells, by inhibiting apoptosis and promoting the proliferation of cancer cells, HSP90 facilitates the survival and growth of cancer cells [6][7][8]. The specific expression of HSP90 when acting as an anti-apoptotic chaperone protein is commonly higher in cancer cells, including prostate cancer [9], leukemia [10], and lung cancer [11]. HSP90B1 is a member of the HSP90 family of genes.…”
Section: Introductionmentioning
confidence: 99%